Synthesis, crystal structure and Hirshfeld surface analysis of a zinc(II) coordination polymer of 5-phenyl-1,3,4-oxadiazole-2-thiolate - Pirimova, Mehribon; Torambetov, Batirbay; Kadirova, Shakhnoza; Ziyaev, Abdukhakim; Gonnade, Rajesh G.; Ashurov, Jamshid (Acta Crystallographica Section E Crystallographic Communications, 2022)
A new zinc coordination polymer with 5-phenyl-1,3,4-oxadiazole-2-thiolate, namely, catena-poly[zinc(II)-bis(μ2-5-phenyl-1,3,4-oxadiazole-2-thiolato)-κ2N3:S;κ2S:N3], [Zn(C8H5N2OS)2]n, was synthesized. The single-crystal X-ray <a class="ref_lookup_orange hideorange" href="https://goldbook.iupac.org/D01712.html" style="text-decoration-line: none; color: rgb(0, 0, 0); font-family: Verdana, Arial, Helvetica, sans-serif;" target="Navigator">diffraction analysis shows that the polymeric structure crystallizes in the centrosymmetric monoclinic C2/c <a class="ref_lookup_yellow hideyellow" href="https://dictionary.iucr.org/Space_group" style="text-decoration-line: none; color: rgb(0, 0, 0); font-family: Verdana, Arial, Helvetica, sans-serif;" target="Navigator">space group. The ZnII atom is coordinated to two S and two N atoms from four crystallographically independent (L) ligands, forming zigzag chains along the [001] direction. This polymer complex forms an eight-membered [Zn–S–C–N–Zn–S–C–N] chair-like ring with two ZnII atoms and two ligand molecules. On the Hirshfeld surface, the largest contributions come from the short contacts such as <a class="ref_lookup_orange hideorange" href="https://goldbook.iupac.org/V06597.html" style="text-decoration-line: none; color: rgb(0, 0, 0); font-family: Verdana, Arial, Helvetica, sans-serif;" target="Navigator">van der Waals forces, including H⋯H, C⋯H and S⋯H. Interactions including N⋯H, O⋯H and C⋯C contacts were also observed; however, their contribution to the overall stability of the <a class="ref_lookup_yellow hideyellow" href="https://dictionary.iucr.org/Lattice" style="text-decoration-line: none; color: rgb(0, 0, 0); font-family: Verdana, Arial, Helvetica, sans-serif;" target="Navigator">crystal lattice is minor.
Keywords: 3; 4-oxadiazole-2-thiol; coordination polymer; Hirshfeld surface analysis; crystal structure; zinc complex; 5-phenyl-1

Synthesis and crystal structure analysis of bis(benzothiazole-2-thiolato-κS)(1,10-phenanthroline-κ2N,N′)zinc(II) - Abdullayeva, Gulchekhra; Torambetov, Batirbay; Kadirova, Shakhnoza; Daminova, Shahlo (Acta Crystallographica Section E, Crystallographic Communications, 2025)

Synthesis and crystal structure of [Sr(urea)(NO3)2]n - Bektursinova, Aysanem; Djumanazarova, Zulfiya; Uzakbergenova, Zamira; Ashurov, Jamshid; Khan, Akram A.; Kadirova, Shakhnoza; Torambetov, Batirbay (Acta crystallographica Section E, Crystallographic communications, 2025)
The crystal structure of poly[di-μ<span style="box-sizing: inherit; line-height: 0; position: relative; vertical-align: baseline; bottom: -0.25em; color: rgb(33, 33, 33); font-family: BlinkMacSystemFont, -apple-system, "Segoe UI", Roboto, Oxygen, Ubuntu, Cantarell, "Fira Sans", "Droid Sans", "Helvetica Neue", sans-serif;">2-nitrato-μ<span style="box-sizing: inherit; line-height: 0; position: relative; vertical-align: baseline; bottom: -0.25em; color: rgb(33, 33, 33); font-family: BlinkMacSystemFont, -apple-system, "Segoe UI", Roboto, Oxygen, Ubuntu, Cantarell, "Fira Sans", "Droid Sans", "Helvetica Neue", sans-serif;">2-urea-strontium(II)], [Sr(NO<span style="box-sizing: inherit; line-height: 0; position: relative; vertical-align: baseline; bottom: -0.25em; color: rgb(33, 33, 33); font-family: BlinkMacSystemFont, -apple-system, "Segoe UI", Roboto, Oxygen, Ubuntu, Cantarell, "Fira Sans", "Droid Sans", "Helvetica Neue", sans-serif;">3)<span style="box-sizing: inherit; line-height: 0; position: relative; vertical-align: baseline; bottom: -0.25em; color: rgb(33, 33, 33); font-family: BlinkMacSystemFont, -apple-system, "Segoe UI", Roboto, Oxygen, Ubuntu, Cantarell, "Fira Sans", "Droid Sans", "Helvetica Neue", sans-serif;">2(CH<span style="box-sizing: inherit; line-height: 0; position: relative; vertical-align: baseline; bottom: -0.25em; color: rgb(33, 33, 33); font-family: BlinkMacSystemFont, -apple-system, "Segoe UI", Roboto, Oxygen, Ubuntu, Cantarell, "Fira Sans", "Droid Sans", "Helvetica Neue", sans-serif;">4N<span style="box-sizing: inherit; line-height: 0; position: relative; vertical-align: baseline; bottom: -0.25em; color: rgb(33, 33, 33); font-family: BlinkMacSystemFont, -apple-system, "Segoe UI", Roboto, Oxygen, Ubuntu, Cantarell, "Fira Sans", "Droid Sans", "Helvetica Neue", sans-serif;">2O)] <span style="box-sizing: inherit; line-height: 0; position: relative; vertical-align: baseline; bottom: -0.25em; color: rgb(33, 33, 33); font-family: BlinkMacSystemFont, -apple-system, "Segoe UI", Roboto, Oxygen, Ubuntu, Cantarell, "Fira Sans", "Droid Sans", "Helvetica Neue", sans-serif;">n , was determined using single-crystal X-ray diffraction. Crystallizing in the ortho-rhom-bic space group <i style="box-sizing: inherit; color: rgb(33, 33, 33); font-family: BlinkMacSystemFont, -apple-system, "Segoe UI", Roboto, Oxygen, Ubuntu, Cantarell, "Fira Sans", "Droid Sans", "Helvetica Neue", sans-serif; font-size: 16px;">Aba2, the asymmetric unit consists of an Sr<span style="box-sizing: inherit; line-height: 0; position: relative; vertical-align: baseline; top: -0.5em; color: rgb(33, 33, 33); font-family: BlinkMacSystemFont, -apple-system, "Segoe UI", Roboto, Oxygen, Ubuntu, Cantarell, "Fira Sans", "Droid Sans", "Helvetica Neue", sans-serif;">II cation, two nitrate anions, and two half urea mol-ecules. The Sr<span style="box-sizing: inherit; line-height: 0; position: relative; vertical-align: baseline; top: -0.5em; color: rgb(33, 33, 33); font-family: BlinkMacSystemFont, -apple-system, "Segoe UI", Roboto, Oxygen, Ubuntu, Cantarell, "Fira Sans", "Droid Sans", "Helvetica Neue", sans-serif;">II cation adopts a distorted deca-hedral geometry coordinated by ten oxygen atoms, with Sr-O bond lengths ranging from 2.573 (3) to 2.847 (5) Å. The nitrate anions act as bidentate ligands, displaying both terminal and bridging coordination modes. The structure features a robust coordination network supported by hydrogen bonding. These results provide insight into the coord-ination behaviour of Sr<span style="box-sizing: inherit; line-height: 0; position: relative; vertical-align: baseline; top: -0.5em; color: rgb(33, 33, 33); font-family: BlinkMacSystemFont, -apple-system, "Segoe UI", Roboto, Oxygen, Ubuntu, Cantarell, "Fira Sans", "Droid Sans", "Helvetica Neue", sans-serif;">II with nitrate and urea ligands, contributing to the understanding of supra-molecular architectures in metal-organic frameworks (MOFs).

Synthesis, crystal structure and Hirshfeld analysis of a novel supramolecular compound [Co(tsc)3]2[Co(cit)2](NO3)4·4H2O - Nuralieva, Guzal; Umirzakova, Oydinoy; Torambetov, Batirbay; Rasulov, Abdusamat; Ashurov, Jamshid; Kadirova, Shakhnoza (Acta Crystallographica Section E-Crystallographic Communications, 2025)
A new cobalt complex, bis[tris(aminothiourea)cobalt(III)] bis[2-(carboxymethyl)-2-hydroxybutanedioato]cobalt(II) tetranitrate tetrahydrate, [Co(CH5N3S)3][Co(C6H6O7)2]0.5(NO3)2·2H2O, designated as [Co(tsc)3]2[Co(cit)2](NO3)4·4H2O, was synthesized. Two crystallographically independent cobalt centers are present. In the first, the central metal atom is chelated by three thiosemicarbazide ligands in a bidentate fashion whereas the second, positioned on a crystallographic inversion center, is hexacoordinated by two citrate anions in a distorted octahedral geometry. Additionally, two water molecules and two nitrate anions are present in the <a class="ref_lookup_yellow hideyellow" href="https://dictionary.iucr.org/Asymmetric_unit" style="text-decoration-line: none; color: rgb(0, 0, 0); font-family: Verdana, Arial, Helvetica, sans-serif;" target="Navigator">asymmetric unit. Hirshfeld surface analysis revealed that the presence of numerous donor and acceptor groups in the complex, which facilitate hydrogen-bonding interactions that contribute significantly to the overall cohesion of the crystal structure.

Synthesis, crystal structure and Hirshfeld surface analysis of 5-methyl-2-[(1,3-thiazol-2-yl)sulfanyl]-1,3,4-thiadiazole - Kinshakova, Ekaterina; Torambetov, Batirbay; Bharty, Manoj K.; Atashov, Aziz; Rasulov, Abdusamat; Kadirova, Shakhnoza; Gonnade, Rajesh G. (Acta Crystallographica Section E Crystallographic Communications, 2025)
The title compound, C<span style="color-scheme: revert; forced-color-adjust: revert; mask: revert; math-depth: revert; position: revert; position-anchor: revert; text-size-adjust: revert; appearance: revert; color: rgb(27, 27, 27); font-family: Cambria, "Cambria Math", Charter, "Times New Roman", Times, stixgeneral, serif; font-feature-settings: revert; font-kerning: revert; font-language-override: revert; font-optical-sizing: revert; font-palette: revert; font-size: revert; font-size-adjust: revert; font-stretch: revert; font-synthesis: revert; font-variant-alternates: revert; font-variant-east-asian: revert; font-variant-emoji: revert; font-variant-numeric: revert; font-variant-position: revert; font-variation-settings: revert; position-area: revert; text-orientation: revert; text-rendering: revert; text-spacing-trim: revert; -webkit-font-smoothing: revert; -webkit-locale: revert; -webkit-text-orientation: revert; -webkit-writing-mode: revert; writing-mode: revert; zoom: revert; accent-color: revert; place-content: revert; place-items: revert; place-self: revert; alignment-baseline: revert; anchor-name: revert; anchor-scope: revert; animation-composition: revert; animation: revert; app-region: revert; aspect-ratio: revert; backdrop-filter: revert; backface-visibility: revert; background-attachment: revert; background-blend-mode: revert; background-clip: revert; background-image: revert; background-origin: revert; background-position: revert; background-repeat: revert; background-size: revert; baseline-shift: revert; baseline-source: revert; block-size: revert; border-block: revert; border: revert; border-radius: revert; border-collapse: revert; border-end-end-radius: revert; border-end-start-radius: revert; border-inline: revert; border-start-end-radius: revert; border-start-start-radius: revert; inset: revert; box-decoration-break: revert; box-shadow: revert; box-sizing: revert; break-after: revert; break-before: revert; break-inside: revert; buffered-rendering: revert; caption-side: revert; caret-animation: revert; caret-color: revert; caret-shape: revert; clear: revert; clip: revert; clip-path: revert; clip-rule: revert; color-interpolation: revert; color-interpolation-filters: revert; color-rendering: revert; columns: revert; column-fill: revert; gap: revert; column-rule: revert; column-span: revert; contain: revert; contain-intrinsic-block-size: revert; contain-intrinsic-size: revert; contain-intrinsic-inline-size: revert; container: revert; content: revert; content-visibility: revert; corner-shape: revert; corner-block-end-shape: revert; corner-block-start-shape: revert; counter-increment: revert; counter-reset: revert; counter-set: revert; cursor: revert; cx: revert; cy: revert; d: revert; display: revert; dominant-baseline: revert; dynamic-range-limit: revert; empty-cells: revert; field-sizing: revert; fill: revert; fill-opacity: revert; fill-rule: revert; filter: revert; flex: revert; flex-flow: revert; float: revert; flood-color: revert; flood-opacity: revert; grid: revert; grid-area: revert; height: revert; hyphenate-character: revert; hyphenate-limit-chars: revert; hyphens: revert; image-orientation: revert; image-rendering: revert; initial-letter: revert; inline-size: revert; inset-block: revert; inset-inline: revert; interactivity: revert; interest-delay: revert; interpolate-size: revert; isolation: revert; lighting-color: revert; line-break: revert; line-height: revert; list-style: revert; margin-block: revert; margin: revert; margin-inline: revert; marker: revert; mask-type: revert; math-shift: revert; math-style: revert; max-block-size: revert; max-height: revert; max-inline-size: revert; max-width: revert; min-block-size: revert; min-height: revert; min-inline-size: revert; min-width: revert; mix-blend-mode: revert; object-fit: revert; object-position: revert; object-view-box: revert; offset: revert; opacity: revert; order: revert; outline: revert; outline-offset: revert; overflow-anchor: revert; overflow-block: revert; overflow-clip-margin: revert; overflow-inline: revert; overflow-wrap: revert; overflow: revert; overlay: revert; overscroll-behavior-block: revert; overscroll-behavior-inline: revert; overscroll-behavior: revert; padding-block: revert; padding: revert; padding-inline: revert; page: revert; page-orientation: revert; paint-order: revert; perspective: revert; perspective-origin: revert; pointer-events: revert; position-try: revert; position-visibility: revert; print-color-adjust: revert; quotes: revert; r: revert; reading-flow: revert; reading-order: revert; resize: revert; rotate: revert; ruby-align: revert; ruby-position: revert; rx: revert; ry: revert; scale: revert; scroll-behavior: revert; scroll-initial-target: revert; scroll-margin-block: revert; scroll-margin: revert; scroll-margin-inline: revert; scroll-marker-group: revert; scroll-padding-block: revert; scroll-padding: revert; scroll-padding-inline: revert; scroll-snap-align: revert; scroll-snap-stop: revert; scroll-snap-type: revert; scroll-target-group: revert; scroll-timeline: revert; scrollbar-color: revert; scrollbar-gutter: revert; scrollbar-width: revert; shape-image-threshold: revert; shape-margin: revert; shape-outside: revert; shape-rendering: revert; size: revert; speak: revert; stop-color: revert; stop-opacity: revert; stroke: revert; stroke-dasharray: revert; stroke-dashoffset: revert; stroke-linecap: revert; stroke-linejoin: revert; stroke-miterlimit: revert; stroke-opacity: revert; stroke-width: revert; tab-size: revert; table-layout: revert; text-align-last: revert; text-anchor: revert; text-autospace: revert; text-box: revert; text-combine-upright: revert; text-decoration-line: revert; text-decoration-skip-ink: revert; text-emphasis: revert; text-emphasis-position: revert; text-justify: revert; text-overflow: revert; text-shadow: revert; text-underline-offset: revert; text-underline-position: revert; text-wrap-style: revert; timeline-scope: revert; touch-action: revert; transform: revert; transform-box: revert; transform-origin: revert; transform-style: revert; transition: revert; translate: revert; user-select: revert; vector-effect: revert; vertical-align: revert; view-timeline: revert; view-transition-class: revert; view-transition-group: revert; view-transition-name: revert; visibility: revert; border-spacing: revert; -webkit-box-align: revert; -webkit-box-decoration-break: revert; -webkit-box-direction: revert; -webkit-box-flex: revert; -webkit-box-ordinal-group: revert; -webkit-box-orient: revert; -webkit-box-pack: revert; -webkit-box-reflect: revert; -webkit-line-break: revert; -webkit-line-clamp: revert; -webkit-mask-box-image: revert; -webkit-rtl-ordering: revert; -webkit-ruby-position: revert; -webkit-tap-highlight-color: revert; -webkit-text-combine: revert; -webkit-text-decorations-in-effect: revert; -webkit-text-fill-color: revert; -webkit-text-security: revert; -webkit-text-stroke-color: revert; -webkit-user-drag: revert; width: revert; will-change: revert; word-break: revert; x: revert; y: revert; z-index: revert;">6H<span style="color-scheme: revert; forced-color-adjust: revert; mask: revert; math-depth: revert; position: revert; position-anchor: revert; text-size-adjust: revert; appearance: revert; color: rgb(27, 27, 27); font-family: Cambria, "Cambria Math", Charter, "Times New Roman", Times, stixgeneral, serif; font-feature-settings: revert; font-kerning: revert; font-language-override: revert; font-optical-sizing: revert; font-palette: revert; font-size: revert; font-size-adjust: revert; font-stretch: revert; font-synthesis: revert; font-variant-alternates: revert; font-variant-east-asian: revert; font-variant-emoji: revert; font-variant-numeric: revert; font-variant-position: revert; font-variation-settings: revert; position-area: revert; text-orientation: revert; text-rendering: revert; text-spacing-trim: revert; -webkit-font-smoothing: revert; -webkit-locale: revert; -webkit-text-orientation: revert; -webkit-writing-mode: revert; writing-mode: revert; zoom: revert; accent-color: revert; place-content: revert; place-items: revert; place-self: revert; alignment-baseline: revert; anchor-name: revert; anchor-scope: revert; animation-composition: revert; animation: revert; app-region: revert; aspect-ratio: revert; backdrop-filter: revert; backface-visibility: revert; background-attachment: revert; background-blend-mode: revert; background-clip: revert; background-image: revert; background-origin: revert; background-position: revert; background-repeat: revert; background-size: revert; baseline-shift: revert; baseline-source: revert; block-size: revert; border-block: revert; border: revert; border-radius: revert; border-collapse: revert; border-end-end-radius: revert; border-end-start-radius: revert; border-inline: revert; border-start-end-radius: revert; border-start-start-radius: revert; inset: revert; box-decoration-break: revert; box-shadow: revert; box-sizing: revert; break-after: revert; break-before: revert; break-inside: revert; buffered-rendering: revert; caption-side: revert; caret-animation: revert; caret-color: revert; caret-shape: revert; clear: revert; clip: revert; clip-path: revert; clip-rule: revert; color-interpolation: revert; color-interpolation-filters: revert; color-rendering: revert; columns: revert; column-fill: revert; gap: revert; column-rule: revert; column-span: revert; contain: revert; contain-intrinsic-block-size: revert; contain-intrinsic-size: revert; contain-intrinsic-inline-size: revert; container: revert; content: revert; content-visibility: revert; corner-shape: revert; corner-block-end-shape: revert; corner-block-start-shape: revert; counter-increment: revert; counter-reset: revert; counter-set: revert; cursor: revert; cx: revert; cy: revert; d: revert; display: revert; dominant-baseline: revert; dynamic-range-limit: revert; empty-cells: revert; field-sizing: revert; fill: revert; fill-opacity: revert; fill-rule: revert; filter: revert; flex: revert; flex-flow: revert; float: revert; flood-color: revert; flood-opacity: revert; grid: revert; grid-area: revert; height: revert; hyphenate-character: revert; hyphenate-limit-chars: revert; hyphens: revert; image-orientation: revert; image-rendering: revert; initial-letter: revert; inline-size: revert; inset-block: revert; inset-inline: revert; interactivity: revert; interest-delay: revert; interpolate-size: revert; isolation: revert; lighting-color: revert; line-break: revert; line-height: revert; list-style: revert; margin-block: revert; margin: revert; margin-inline: revert; marker: revert; mask-type: revert; math-shift: revert; math-style: revert; max-block-size: revert; max-height: revert; max-inline-size: revert; max-width: revert; min-block-size: revert; min-height: revert; min-inline-size: revert; min-width: revert; mix-blend-mode: revert; object-fit: revert; object-position: revert; object-view-box: revert; offset: revert; opacity: revert; order: revert; outline: revert; outline-offset: revert; overflow-anchor: revert; overflow-block: revert; overflow-clip-margin: revert; overflow-inline: revert; overflow-wrap: revert; overflow: revert; overlay: revert; overscroll-behavior-block: revert; overscroll-behavior-inline: revert; overscroll-behavior: revert; padding-block: revert; padding: revert; padding-inline: revert; page: revert; page-orientation: revert; paint-order: revert; perspective: revert; perspective-origin: revert; pointer-events: revert; position-try: revert; position-visibility: revert; print-color-adjust: revert; quotes: revert; r: revert; reading-flow: revert; reading-order: revert; resize: revert; rotate: revert; ruby-align: revert; ruby-position: revert; rx: revert; ry: revert; scale: revert; scroll-behavior: revert; scroll-initial-target: revert; scroll-margin-block: revert; scroll-margin: revert; scroll-margin-inline: revert; scroll-marker-group: revert; scroll-padding-block: revert; scroll-padding: revert; scroll-padding-inline: revert; scroll-snap-align: revert; scroll-snap-stop: revert; scroll-snap-type: revert; scroll-target-group: revert; scroll-timeline: revert; scrollbar-color: revert; scrollbar-gutter: revert; scrollbar-width: revert; shape-image-threshold: revert; shape-margin: revert; shape-outside: revert; shape-rendering: revert; size: revert; speak: revert; stop-color: revert; stop-opacity: revert; stroke: revert; stroke-dasharray: revert; stroke-dashoffset: revert; stroke-linecap: revert; stroke-linejoin: revert; stroke-miterlimit: revert; stroke-opacity: revert; stroke-width: revert; tab-size: revert; table-layout: revert; text-align-last: revert; text-anchor: revert; text-autospace: revert; text-box: revert; text-combine-upright: revert; text-decoration-line: revert; text-decoration-skip-ink: revert; text-emphasis: revert; text-emphasis-position: revert; text-justify: revert; text-overflow: revert; text-shadow: revert; text-underline-offset: revert; text-underline-position: revert; text-wrap-style: revert; timeline-scope: revert; touch-action: revert; transform: revert; transform-box: revert; transform-origin: revert; transform-style: revert; transition: revert; translate: revert; user-select: revert; vector-effect: revert; vertical-align: revert; view-timeline: revert; view-transition-class: revert; view-transition-group: revert; view-transition-name: revert; visibility: revert; border-spacing: revert; -webkit-box-align: revert; -webkit-box-decoration-break: revert; -webkit-box-direction: revert; -webkit-box-flex: revert; -webkit-box-ordinal-group: revert; -webkit-box-orient: revert; -webkit-box-pack: revert; -webkit-box-reflect: revert; -webkit-line-break: revert; -webkit-line-clamp: revert; -webkit-mask-box-image: revert; -webkit-rtl-ordering: revert; -webkit-ruby-position: revert; -webkit-tap-highlight-color: revert; -webkit-text-combine: revert; -webkit-text-decorations-in-effect: revert; -webkit-text-fill-color: revert; -webkit-text-security: revert; -webkit-text-stroke-color: revert; -webkit-user-drag: revert; width: revert; will-change: revert; word-break: revert; x: revert; y: revert; z-index: revert;">5N<span style="color-scheme: revert; forced-color-adjust: revert; mask: revert; math-depth: revert; position: revert; position-anchor: revert; text-size-adjust: revert; appearance: revert; color: rgb(27, 27, 27); font-family: Cambria, "Cambria Math", Charter, "Times New Roman", Times, stixgeneral, serif; font-feature-settings: revert; font-kerning: revert; font-language-override: revert; font-optical-sizing: revert; font-palette: revert; font-size: revert; font-size-adjust: revert; font-stretch: revert; font-synthesis: revert; font-variant-alternates: revert; font-variant-east-asian: revert; font-variant-emoji: revert; font-variant-numeric: revert; font-variant-position: revert; font-variation-settings: revert; position-area: revert; text-orientation: revert; text-rendering: revert; text-spacing-trim: revert; -webkit-font-smoothing: revert; -webkit-locale: revert; -webkit-text-orientation: revert; -webkit-writing-mode: revert; writing-mode: revert; zoom: revert; accent-color: revert; place-content: revert; place-items: revert; place-self: revert; alignment-baseline: revert; anchor-name: revert; anchor-scope: revert; animation-composition: revert; animation: revert; app-region: revert; aspect-ratio: revert; backdrop-filter: revert; backface-visibility: revert; background-attachment: revert; background-blend-mode: revert; background-clip: revert; background-image: revert; background-origin: revert; background-position: revert; background-repeat: revert; background-size: revert; baseline-shift: revert; baseline-source: revert; block-size: revert; border-block: revert; border: revert; border-radius: revert; border-collapse: revert; border-end-end-radius: revert; border-end-start-radius: revert; border-inline: revert; border-start-end-radius: revert; border-start-start-radius: revert; inset: revert; box-decoration-break: revert; box-shadow: revert; box-sizing: revert; break-after: revert; break-before: revert; break-inside: revert; buffered-rendering: revert; caption-side: revert; caret-animation: revert; caret-color: revert; caret-shape: revert; clear: revert; clip: revert; clip-path: revert; clip-rule: revert; color-interpolation: revert; color-interpolation-filters: revert; color-rendering: revert; columns: revert; column-fill: revert; gap: revert; column-rule: revert; column-span: revert; contain: revert; contain-intrinsic-block-size: revert; contain-intrinsic-size: revert; contain-intrinsic-inline-size: revert; container: revert; content: revert; content-visibility: revert; corner-shape: revert; corner-block-end-shape: revert; corner-block-start-shape: revert; counter-increment: revert; counter-reset: revert; counter-set: revert; cursor: revert; cx: revert; cy: revert; d: revert; display: revert; dominant-baseline: revert; dynamic-range-limit: revert; empty-cells: revert; field-sizing: revert; fill: revert; fill-opacity: revert; fill-rule: revert; filter: revert; flex: revert; flex-flow: revert; float: revert; flood-color: revert; flood-opacity: revert; grid: revert; grid-area: revert; height: revert; hyphenate-character: revert; hyphenate-limit-chars: revert; hyphens: revert; image-orientation: revert; image-rendering: revert; initial-letter: revert; inline-size: revert; inset-block: revert; inset-inline: revert; interactivity: revert; interest-delay: revert; interpolate-size: revert; isolation: revert; lighting-color: revert; line-break: revert; line-height: revert; list-style: revert; margin-block: revert; margin: revert; margin-inline: revert; marker: revert; mask-type: revert; math-shift: revert; math-style: revert; max-block-size: revert; max-height: revert; max-inline-size: revert; max-width: revert; min-block-size: revert; min-height: revert; min-inline-size: revert; min-width: revert; mix-blend-mode: revert; object-fit: revert; object-position: revert; object-view-box: revert; offset: revert; opacity: revert; order: revert; outline: revert; outline-offset: revert; overflow-anchor: revert; overflow-block: revert; overflow-clip-margin: revert; overflow-inline: revert; overflow-wrap: revert; overflow: revert; overlay: revert; overscroll-behavior-block: revert; overscroll-behavior-inline: revert; overscroll-behavior: revert; padding-block: revert; padding: revert; padding-inline: revert; page: revert; page-orientation: revert; paint-order: revert; perspective: revert; perspective-origin: revert; pointer-events: revert; position-try: revert; position-visibility: revert; print-color-adjust: revert; quotes: revert; r: revert; reading-flow: revert; reading-order: revert; resize: revert; rotate: revert; ruby-align: revert; ruby-position: revert; rx: revert; ry: revert; scale: revert; scroll-behavior: revert; scroll-initial-target: revert; scroll-margin-block: revert; scroll-margin: revert; scroll-margin-inline: revert; scroll-marker-group: revert; scroll-padding-block: revert; scroll-padding: revert; scroll-padding-inline: revert; scroll-snap-align: revert; scroll-snap-stop: revert; scroll-snap-type: revert; scroll-target-group: revert; scroll-timeline: revert; scrollbar-color: revert; scrollbar-gutter: revert; scrollbar-width: revert; shape-image-threshold: revert; shape-margin: revert; shape-outside: revert; shape-rendering: revert; size: revert; speak: revert; stop-color: revert; stop-opacity: revert; stroke: revert; stroke-dasharray: revert; stroke-dashoffset: revert; stroke-linecap: revert; stroke-linejoin: revert; stroke-miterlimit: revert; stroke-opacity: revert; stroke-width: revert; tab-size: revert; table-layout: revert; text-align-last: revert; text-anchor: revert; text-autospace: revert; text-box: revert; text-combine-upright: revert; text-decoration-line: revert; text-decoration-skip-ink: revert; text-emphasis: revert; text-emphasis-position: revert; text-justify: revert; text-overflow: revert; text-shadow: revert; text-underline-offset: revert; text-underline-position: revert; text-wrap-style: revert; timeline-scope: revert; touch-action: revert; transform: revert; transform-box: revert; transform-origin: revert; transform-style: revert; transition: revert; translate: revert; user-select: revert; vector-effect: revert; vertical-align: revert; view-timeline: revert; view-transition-class: revert; view-transition-group: revert; view-transition-name: revert; visibility: revert; border-spacing: revert; -webkit-box-align: revert; -webkit-box-decoration-break: revert; -webkit-box-direction: revert; -webkit-box-flex: revert; -webkit-box-ordinal-group: revert; -webkit-box-orient: revert; -webkit-box-pack: revert; -webkit-box-reflect: revert; -webkit-line-break: revert; -webkit-line-clamp: revert; -webkit-mask-box-image: revert; -webkit-rtl-ordering: revert; -webkit-ruby-position: revert; -webkit-tap-highlight-color: revert; -webkit-text-combine: revert; -webkit-text-decorations-in-effect: revert; -webkit-text-fill-color: revert; -webkit-text-security: revert; -webkit-text-stroke-color: revert; -webkit-user-drag: revert; width: revert; will-change: revert; word-break: revert; x: revert; y: revert; z-index: revert;">3S<span style="color-scheme: revert; forced-color-adjust: revert; mask: revert; math-depth: revert; position: revert; position-anchor: revert; text-size-adjust: revert; appearance: revert; color: rgb(27, 27, 27); font-family: Cambria, "Cambria Math", Charter, "Times New Roman", Times, stixgeneral, serif; font-feature-settings: revert; font-kerning: revert; font-language-override: revert; font-optical-sizing: revert; font-palette: revert; font-size: revert; font-size-adjust: revert; font-stretch: revert; font-synthesis: revert; font-variant-alternates: revert; font-variant-east-asian: revert; font-variant-emoji: revert; font-variant-numeric: revert; font-variant-position: revert; font-variation-settings: revert; position-area: revert; text-orientation: revert; text-rendering: revert; text-spacing-trim: revert; -webkit-font-smoothing: revert; -webkit-locale: revert; -webkit-text-orientation: revert; -webkit-writing-mode: revert; writing-mode: revert; zoom: revert; accent-color: revert; place-content: revert; place-items: revert; place-self: revert; alignment-baseline: revert; anchor-name: revert; anchor-scope: revert; animation-composition: revert; animation: revert; app-region: revert; aspect-ratio: revert; backdrop-filter: revert; backface-visibility: revert; background-attachment: revert; background-blend-mode: revert; background-clip: revert; background-image: revert; background-origin: revert; background-position: revert; background-repeat: revert; background-size: revert; baseline-shift: revert; baseline-source: revert; block-size: revert; border-block: revert; border: revert; border-radius: revert; border-collapse: revert; border-end-end-radius: revert; border-end-start-radius: revert; border-inline: revert; border-start-end-radius: revert; border-start-start-radius: revert; inset: revert; box-decoration-break: revert; box-shadow: revert; box-sizing: revert; break-after: revert; break-before: revert; break-inside: revert; buffered-rendering: revert; caption-side: revert; caret-animation: revert; caret-color: revert; caret-shape: revert; clear: revert; clip: revert; clip-path: revert; clip-rule: revert; color-interpolation: revert; color-interpolation-filters: revert; color-rendering: revert; columns: revert; column-fill: revert; gap: revert; column-rule: revert; column-span: revert; contain: revert; contain-intrinsic-block-size: revert; contain-intrinsic-size: revert; contain-intrinsic-inline-size: revert; container: revert; content: revert; content-visibility: revert; corner-shape: revert; corner-block-end-shape: revert; corner-block-start-shape: revert; counter-increment: revert; counter-reset: revert; counter-set: revert; cursor: revert; cx: revert; cy: revert; d: revert; display: revert; dominant-baseline: revert; dynamic-range-limit: revert; empty-cells: revert; field-sizing: revert; fill: revert; fill-opacity: revert; fill-rule: revert; filter: revert; flex: revert; flex-flow: revert; float: revert; flood-color: revert; flood-opacity: revert; grid: revert; grid-area: revert; height: revert; hyphenate-character: revert; hyphenate-limit-chars: revert; hyphens: revert; image-orientation: revert; image-rendering: revert; initial-letter: revert; inline-size: revert; inset-block: revert; inset-inline: revert; interactivity: revert; interest-delay: revert; interpolate-size: revert; isolation: revert; lighting-color: revert; line-break: revert; line-height: revert; list-style: revert; margin-block: revert; margin: revert; margin-inline: revert; marker: revert; mask-type: revert; math-shift: revert; math-style: revert; max-block-size: revert; max-height: revert; max-inline-size: revert; max-width: revert; min-block-size: revert; min-height: revert; min-inline-size: revert; min-width: revert; mix-blend-mode: revert; object-fit: revert; object-position: revert; object-view-box: revert; offset: revert; opacity: revert; order: revert; outline: revert; outline-offset: revert; overflow-anchor: revert; overflow-block: revert; overflow-clip-margin: revert; overflow-inline: revert; overflow-wrap: revert; overflow: revert; overlay: revert; overscroll-behavior-block: revert; overscroll-behavior-inline: revert; overscroll-behavior: revert; padding-block: revert; padding: revert; padding-inline: revert; page: revert; page-orientation: revert; paint-order: revert; perspective: revert; perspective-origin: revert; pointer-events: revert; position-try: revert; position-visibility: revert; print-color-adjust: revert; quotes: revert; r: revert; reading-flow: revert; reading-order: revert; resize: revert; rotate: revert; ruby-align: revert; ruby-position: revert; rx: revert; ry: revert; scale: revert; scroll-behavior: revert; scroll-initial-target: revert; scroll-margin-block: revert; scroll-margin: revert; scroll-margin-inline: revert; scroll-marker-group: revert; scroll-padding-block: revert; scroll-padding: revert; scroll-padding-inline: revert; scroll-snap-align: revert; scroll-snap-stop: revert; scroll-snap-type: revert; scroll-target-group: revert; scroll-timeline: revert; scrollbar-color: revert; scrollbar-gutter: revert; scrollbar-width: revert; shape-image-threshold: revert; shape-margin: revert; shape-outside: revert; shape-rendering: revert; size: revert; speak: revert; stop-color: revert; stop-opacity: revert; stroke: revert; stroke-dasharray: revert; stroke-dashoffset: revert; stroke-linecap: revert; stroke-linejoin: revert; stroke-miterlimit: revert; stroke-opacity: revert; stroke-width: revert; tab-size: revert; table-layout: revert; text-align-last: revert; text-anchor: revert; text-autospace: revert; text-box: revert; text-combine-upright: revert; text-decoration-line: revert; text-decoration-skip-ink: revert; text-emphasis: revert; text-emphasis-position: revert; text-justify: revert; text-overflow: revert; text-shadow: revert; text-underline-offset: revert; text-underline-position: revert; text-wrap-style: revert; timeline-scope: revert; touch-action: revert; transform: revert; transform-box: revert; transform-origin: revert; transform-style: revert; transition: revert; translate: revert; user-select: revert; vector-effect: revert; vertical-align: revert; view-timeline: revert; view-transition-class: revert; view-transition-group: revert; view-transition-name: revert; visibility: revert; border-spacing: revert; -webkit-box-align: revert; -webkit-box-decoration-break: revert; -webkit-box-direction: revert; -webkit-box-flex: revert; -webkit-box-ordinal-group: revert; -webkit-box-orient: revert; -webkit-box-pack: revert; -webkit-box-reflect: revert; -webkit-line-break: revert; -webkit-line-clamp: revert; -webkit-mask-box-image: revert; -webkit-rtl-ordering: revert; -webkit-ruby-position: revert; -webkit-tap-highlight-color: revert; -webkit-text-combine: revert; -webkit-text-decorations-in-effect: revert; -webkit-text-fill-color: revert; -webkit-text-security: revert; -webkit-text-stroke-color: revert; -webkit-user-drag: revert; width: revert; will-change: revert; word-break: revert; x: revert; y: revert; z-index: revert;">3, consists of two biologically relevant heterocyclic units, suggesting potential biological activity and possible use as a ligand in metal complexation. The compound crystallizes in the monoclinic space group P2<span style="color-scheme: revert; forced-color-adjust: revert; mask: revert; math-depth: revert; position: revert; position-anchor: revert; text-size-adjust: revert; appearance: revert; color: rgb(27, 27, 27); font-family: Cambria, "Cambria Math", Charter, "Times New Roman", Times, stixgeneral, serif; font-feature-settings: revert; font-kerning: revert; font-language-override: revert; font-optical-sizing: revert; font-palette: revert; font-size: revert; font-size-adjust: revert; font-stretch: revert; font-synthesis: revert; font-variant-alternates: revert; font-variant-east-asian: revert; font-variant-emoji: revert; font-variant-numeric: revert; font-variant-position: revert; font-variation-settings: revert; position-area: revert; text-orientation: revert; text-rendering: revert; text-spacing-trim: revert; -webkit-font-smoothing: revert; -webkit-locale: revert; -webkit-text-orientation: revert; -webkit-writing-mode: revert; writing-mode: revert; zoom: revert; accent-color: revert; place-content: revert; place-items: revert; place-self: revert; alignment-baseline: revert; anchor-name: revert; anchor-scope: revert; animation-composition: revert; animation: revert; app-region: revert; aspect-ratio: revert; backdrop-filter: revert; backface-visibility: revert; background-attachment: revert; background-blend-mode: revert; background-clip: revert; background-image: revert; background-origin: revert; background-position: revert; background-repeat: revert; background-size: revert; baseline-shift: revert; baseline-source: revert; block-size: revert; border-block: revert; border: revert; border-radius: revert; border-collapse: revert; border-end-end-radius: revert; border-end-start-radius: revert; border-inline: revert; border-start-end-radius: revert; border-start-start-radius: revert; inset: revert; box-decoration-break: revert; box-shadow: revert; box-sizing: revert; break-after: revert; break-before: revert; break-inside: revert; buffered-rendering: revert; caption-side: revert; caret-animation: revert; caret-color: revert; caret-shape: revert; clear: revert; clip: revert; clip-path: revert; clip-rule: revert; color-interpolation: revert; color-interpolation-filters: revert; color-rendering: revert; columns: revert; column-fill: revert; gap: revert; column-rule: revert; column-span: revert; contain: revert; contain-intrinsic-block-size: revert; contain-intrinsic-size: revert; contain-intrinsic-inline-size: revert; container: revert; content: revert; content-visibility: revert; corner-shape: revert; corner-block-end-shape: revert; corner-block-start-shape: revert; counter-increment: revert; counter-reset: revert; counter-set: revert; cursor: revert; cx: revert; cy: revert; d: revert; display: revert; dominant-baseline: revert; dynamic-range-limit: revert; empty-cells: revert; field-sizing: revert; fill: revert; fill-opacity: revert; fill-rule: revert; filter: revert; flex: revert; flex-flow: revert; float: revert; flood-color: revert; flood-opacity: revert; grid: revert; grid-area: revert; height: revert; hyphenate-character: revert; hyphenate-limit-chars: revert; hyphens: revert; image-orientation: revert; image-rendering: revert; initial-letter: revert; inline-size: revert; inset-block: revert; inset-inline: revert; interactivity: revert; interest-delay: revert; interpolate-size: revert; isolation: revert; lighting-color: revert; line-break: revert; line-height: revert; list-style: revert; margin-block: revert; margin: revert; margin-inline: revert; marker: revert; mask-type: revert; math-shift: revert; math-style: revert; max-block-size: revert; max-height: revert; max-inline-size: revert; max-width: revert; min-block-size: revert; min-height: revert; min-inline-size: revert; min-width: revert; mix-blend-mode: revert; object-fit: revert; object-position: revert; object-view-box: revert; offset: revert; opacity: revert; order: revert; outline: revert; outline-offset: revert; overflow-anchor: revert; overflow-block: revert; overflow-clip-margin: revert; overflow-inline: revert; overflow-wrap: revert; overflow: revert; overlay: revert; overscroll-behavior-block: revert; overscroll-behavior-inline: revert; overscroll-behavior: revert; padding-block: revert; padding: revert; padding-inline: revert; page: revert; page-orientation: revert; paint-order: revert; perspective: revert; perspective-origin: revert; pointer-events: revert; position-try: revert; position-visibility: revert; print-color-adjust: revert; quotes: revert; r: revert; reading-flow: revert; reading-order: revert; resize: revert; rotate: revert; ruby-align: revert; ruby-position: revert; rx: revert; ry: revert; scale: revert; scroll-behavior: revert; scroll-initial-target: revert; scroll-margin-block: revert; scroll-margin: revert; scroll-margin-inline: revert; scroll-marker-group: revert; scroll-padding-block: revert; scroll-padding: revert; scroll-padding-inline: revert; scroll-snap-align: revert; scroll-snap-stop: revert; scroll-snap-type: revert; scroll-target-group: revert; scroll-timeline: revert; scrollbar-color: revert; scrollbar-gutter: revert; scrollbar-width: revert; shape-image-threshold: revert; shape-margin: revert; shape-outside: revert; shape-rendering: revert; size: revert; speak: revert; stop-color: revert; stop-opacity: revert; stroke: revert; stroke-dasharray: revert; stroke-dashoffset: revert; stroke-linecap: revert; stroke-linejoin: revert; stroke-miterlimit: revert; stroke-opacity: revert; stroke-width: revert; tab-size: revert; table-layout: revert; text-align-last: revert; text-anchor: revert; text-autospace: revert; text-box: revert; text-combine-upright: revert; text-decoration-line: revert; text-decoration-skip-ink: revert; text-emphasis: revert; text-emphasis-position: revert; text-justify: revert; text-overflow: revert; text-shadow: revert; text-underline-offset: revert; text-underline-position: revert; text-wrap-style: revert; timeline-scope: revert; touch-action: revert; transform: revert; transform-box: revert; transform-origin: revert; transform-style: revert; transition: revert; translate: revert; user-select: revert; vector-effect: revert; vertical-align: revert; view-timeline: revert; view-transition-class: revert; view-transition-group: revert; view-transition-name: revert; visibility: revert; border-spacing: revert; -webkit-box-align: revert; -webkit-box-decoration-break: revert; -webkit-box-direction: revert; -webkit-box-flex: revert; -webkit-box-ordinal-group: revert; -webkit-box-orient: revert; -webkit-box-pack: revert; -webkit-box-reflect: revert; -webkit-line-break: revert; -webkit-line-clamp: revert; -webkit-mask-box-image: revert; -webkit-rtl-ordering: revert; -webkit-ruby-position: revert; -webkit-tap-highlight-color: revert; -webkit-text-combine: revert; -webkit-text-decorations-in-effect: revert; -webkit-text-fill-color: revert; -webkit-text-security: revert; -webkit-text-stroke-color: revert; -webkit-user-drag: revert; width: revert; will-change: revert; word-break: revert; x: revert; y: revert; z-index: revert;">1/c and features non-classical intermolecular C—H⋯N hydrogen bonds, along with π–π stacking interactions that contribute to the crystal cohesion. Hirshfeld surface analysis highlights significant intermolecular interactions including, among others, N⋯H/H⋯N, S⋯H/H⋯S, and S⋯C/C⋯S contacts.

Synthesis, crystal structure and Hirshfeld surface analysis of a coordination compound of cadmium nitrate with 2-amino-benzoxazole - Razzoqova, Surayyo; Ruzimov, Yodgor; Toshov, Akobir; Torambetov, Batirbay; Ibragimov, Aziz; Ashurov, Jamshid; Kadirova, Shakhnoza (Acta Crystallographica Section E, Crystallographic Communications, 2025)
A coordination complex of cadmium nitrate [Cd(NO<span style="box-sizing: inherit; line-height: 0; position: relative; vertical-align: baseline; bottom: -0.25em; color: rgb(33, 33, 33); font-family: BlinkMacSystemFont, -apple-system, "Segoe UI", Roboto, Oxygen, Ubuntu, Cantarell, "Fira Sans", "Droid Sans", "Helvetica Neue", sans-serif;">3)<span style="box-sizing: inherit; line-height: 0; position: relative; vertical-align: baseline; bottom: -0.25em; color: rgb(33, 33, 33); font-family: BlinkMacSystemFont, -apple-system, "Segoe UI", Roboto, Oxygen, Ubuntu, Cantarell, "Fira Sans", "Droid Sans", "Helvetica Neue", sans-serif;">2] with 2-amino-benzaxole (2AB; C<span style="box-sizing: inherit; line-height: 0; position: relative; vertical-align: baseline; bottom: -0.25em; color: rgb(33, 33, 33); font-family: BlinkMacSystemFont, -apple-system, "Segoe UI", Roboto, Oxygen, Ubuntu, Cantarell, "Fira Sans", "Droid Sans", "Helvetica Neue", sans-serif;">7H<span style="box-sizing: inherit; line-height: 0; position: relative; vertical-align: baseline; bottom: -0.25em; color: rgb(33, 33, 33); font-family: BlinkMacSystemFont, -apple-system, "Segoe UI", Roboto, Oxygen, Ubuntu, Cantarell, "Fira Sans", "Droid Sans", "Helvetica Neue", sans-serif;">6N<span style="box-sizing: inherit; line-height: 0; position: relative; vertical-align: baseline; bottom: -0.25em; color: rgb(33, 33, 33); font-family: BlinkMacSystemFont, -apple-system, "Segoe UI", Roboto, Oxygen, Ubuntu, Cantarell, "Fira Sans", "Droid Sans", "Helvetica Neue", sans-serif;">2O), namely, tetra-kis-(2-amino-benzoxazole-κ<i style="box-sizing: inherit; color: rgb(33, 33, 33); font-family: BlinkMacSystemFont, -apple-system, "Segoe UI", Roboto, Oxygen, Ubuntu, Cantarell, "Fira Sans", "Droid Sans", "Helvetica Neue", sans-serif; font-size: 16px;">N <span style="box-sizing: inherit; line-height: 0; position: relative; vertical-align: baseline; top: -0.5em; color: rgb(33, 33, 33); font-family: BlinkMacSystemFont, -apple-system, "Segoe UI", Roboto, Oxygen, Ubuntu, Cantarell, "Fira Sans", "Droid Sans", "Helvetica Neue", sans-serif;">1)bis-(nitrato-κ<i style="box-sizing: inherit; color: rgb(33, 33, 33); font-family: BlinkMacSystemFont, -apple-system, "Segoe UI", Roboto, Oxygen, Ubuntu, Cantarell, "Fira Sans", "Droid Sans", "Helvetica Neue", sans-serif; font-size: 16px;">O)cadmium(II), [Cd(NO<span style="box-sizing: inherit; line-height: 0; position: relative; vertical-align: baseline; bottom: -0.25em; color: rgb(33, 33, 33); font-family: BlinkMacSystemFont, -apple-system, "Segoe UI", Roboto, Oxygen, Ubuntu, Cantarell, "Fira Sans", "Droid Sans", "Helvetica Neue", sans-serif;">3)<span style="box-sizing: inherit; line-height: 0; position: relative; vertical-align: baseline; bottom: -0.25em; color: rgb(33, 33, 33); font-family: BlinkMacSystemFont, -apple-system, "Segoe UI", Roboto, Oxygen, Ubuntu, Cantarell, "Fira Sans", "Droid Sans", "Helvetica Neue", sans-serif;">2(2AB)<span style="box-sizing: inherit; line-height: 0; position: relative; vertical-align: baseline; bottom: -0.25em; color: rgb(33, 33, 33); font-family: BlinkMacSystemFont, -apple-system, "Segoe UI", Roboto, Oxygen, Ubuntu, Cantarell, "Fira Sans", "Droid Sans", "Helvetica Neue", sans-serif;">4], has been synthesized from ethanol solutions of Cd(NO<span style="box-sizing: inherit; line-height: 0; position: relative; vertical-align: baseline; bottom: -0.25em; color: rgb(33, 33, 33); font-family: BlinkMacSystemFont, -apple-system, "Segoe UI", Roboto, Oxygen, Ubuntu, Cantarell, "Fira Sans", "Droid Sans", "Helvetica Neue", sans-serif;">3)<span style="box-sizing: inherit; line-height: 0; position: relative; vertical-align: baseline; bottom: -0.25em; color: rgb(33, 33, 33); font-family: BlinkMacSystemFont, -apple-system, "Segoe UI", Roboto, Oxygen, Ubuntu, Cantarell, "Fira Sans", "Droid Sans", "Helvetica Neue", sans-serif;">2·H<span style="box-sizing: inherit; line-height: 0; position: relative; vertical-align: baseline; bottom: -0.25em; color: rgb(33, 33, 33); font-family: BlinkMacSystemFont, -apple-system, "Segoe UI", Roboto, Oxygen, Ubuntu, Cantarell, "Fira Sans", "Droid Sans", "Helvetica Neue", sans-serif;">2O and 2AB. The asymmetric unit comprises half a mol-ecule of [Cd(NO<span style="box-sizing: inherit; line-height: 0; position: relative; vertical-align: baseline; bottom: -0.25em; color: rgb(33, 33, 33); font-family: BlinkMacSystemFont, -apple-system, "Segoe UI", Roboto, Oxygen, Ubuntu, Cantarell, "Fira Sans", "Droid Sans", "Helvetica Neue", sans-serif;">3)<span style="box-sizing: inherit; line-height: 0; position: relative; vertical-align: baseline; bottom: -0.25em; color: rgb(33, 33, 33); font-family: BlinkMacSystemFont, -apple-system, "Segoe UI", Roboto, Oxygen, Ubuntu, Cantarell, "Fira Sans", "Droid Sans", "Helvetica Neue", sans-serif;">2(2AB)<span style="box-sizing: inherit; line-height: 0; position: relative; vertical-align: baseline; bottom: -0.25em; color: rgb(33, 33, 33); font-family: BlinkMacSystemFont, -apple-system, "Segoe UI", Roboto, Oxygen, Ubuntu, Cantarell, "Fira Sans", "Droid Sans", "Helvetica Neue", sans-serif;">4], with the Cd<span style="box-sizing: inherit; line-height: 0; position: relative; vertical-align: baseline; top: -0.5em; color: rgb(33, 33, 33); font-family: BlinkMacSystemFont, -apple-system, "Segoe UI", Roboto, Oxygen, Ubuntu, Cantarell, "Fira Sans", "Droid Sans", "Helvetica Neue", sans-serif;">II atom positioned on a twofold rotation axis. In the completed mol-ecular complex, four 2AB ligands and two nitrate anions each coordinate monodentately to the Cd<span style="box-sizing: inherit; line-height: 0; position: relative; vertical-align: baseline; top: -0.5em; color: rgb(33, 33, 33); font-family: BlinkMacSystemFont, -apple-system, "Segoe UI", Roboto, Oxygen, Ubuntu, Cantarell, "Fira Sans", "Droid Sans", "Helvetica Neue", sans-serif;">II atom, leading to a distorted octa-hedral coordination environment. The crystal structure of [Cd(NO<span style="box-sizing: inherit; line-height: 0; position: relative; vertical-align: baseline; bottom: -0.25em; color: rgb(33, 33, 33); font-family: BlinkMacSystemFont, -apple-system, "Segoe UI", Roboto, Oxygen, Ubuntu, Cantarell, "Fira Sans", "Droid Sans", "Helvetica Neue", sans-serif;">3)<span style="box-sizing: inherit; line-height: 0; position: relative; vertical-align: baseline; bottom: -0.25em; color: rgb(33, 33, 33); font-family: BlinkMacSystemFont, -apple-system, "Segoe UI", Roboto, Oxygen, Ubuntu, Cantarell, "Fira Sans", "Droid Sans", "Helvetica Neue", sans-serif;">2(2AB)<span style="box-sizing: inherit; line-height: 0; position: relative; vertical-align: baseline; bottom: -0.25em; color: rgb(33, 33, 33); font-family: BlinkMacSystemFont, -apple-system, "Segoe UI", Roboto, Oxygen, Ubuntu, Cantarell, "Fira Sans", "Droid Sans", "Helvetica Neue", sans-serif;">4] exhibits several N-H⋯O inter-actions, resulting in the formation of a layered assembly parallel to (001). Hishfeld surface analysis was used to qu-antify the inter-molecular inter-actions.

Synthesis, crystal structure and Hirshfeld surface analysis of a coordination compound of silver nitrate with 2-amino-benzoxazole - Razzoqova, Surayyo; Sadullayeva, Sojida; Erkinov, Sirojiddin; Torambetov, Batirbay; Alieva, Guloy; Yakhshieva, Zukhra; Ashurov, Jamshid; Kadirova, Shakhnoza (Acta Crystallographica Section E Crystallographic Communications, 2025)
The coordination complex of 2-amino-benzaxole (2AB) with silver(I), namely, bis(2-aminobenzoxazole-κ<i style="box-sizing: inherit; color: rgb(33, 33, 33); font-family: BlinkMacSystemFont, -apple-system, "Segoe UI", Roboto, Oxygen, Ubuntu, Cantarell, "Fira Sans", "Droid Sans", "Helvetica Neue", sans-serif; font-size: 16px;">N)silver(I) nitrate-bis(2-aminobenzoxazole (1/2), [Ag(C<span style="box-sizing: inherit; line-height: 0; position: relative; vertical-align: baseline; bottom: -0.25em; color: rgb(33, 33, 33); font-family: BlinkMacSystemFont, -apple-system, "Segoe UI", Roboto, Oxygen, Ubuntu, Cantarell, "Fira Sans", "Droid Sans", "Helvetica Neue", sans-serif;">7H<span style="box-sizing: inherit; line-height: 0; position: relative; vertical-align: baseline; bottom: -0.25em; color: rgb(33, 33, 33); font-family: BlinkMacSystemFont, -apple-system, "Segoe UI", Roboto, Oxygen, Ubuntu, Cantarell, "Fira Sans", "Droid Sans", "Helvetica Neue", sans-serif;">6N<span style="box-sizing: inherit; line-height: 0; position: relative; vertical-align: baseline; bottom: -0.25em; color: rgb(33, 33, 33); font-family: BlinkMacSystemFont, -apple-system, "Segoe UI", Roboto, Oxygen, Ubuntu, Cantarell, "Fira Sans", "Droid Sans", "Helvetica Neue", sans-serif;">2O)<span style="box-sizing: inherit; line-height: 0; position: relative; vertical-align: baseline; bottom: -0.25em; color: rgb(33, 33, 33); font-family: BlinkMacSystemFont, -apple-system, "Segoe UI", Roboto, Oxygen, Ubuntu, Cantarell, "Fira Sans", "Droid Sans", "Helvetica Neue", sans-serif;">2]NO<span style="box-sizing: inherit; line-height: 0; position: relative; vertical-align: baseline; bottom: -0.25em; color: rgb(33, 33, 33); font-family: BlinkMacSystemFont, -apple-system, "Segoe UI", Roboto, Oxygen, Ubuntu, Cantarell, "Fira Sans", "Droid Sans", "Helvetica Neue", sans-serif;">3·2C<span style="box-sizing: inherit; line-height: 0; position: relative; vertical-align: baseline; bottom: -0.25em; color: rgb(33, 33, 33); font-family: BlinkMacSystemFont, -apple-system, "Segoe UI", Roboto, Oxygen, Ubuntu, Cantarell, "Fira Sans", "Droid Sans", "Helvetica Neue", sans-serif;">7H<span style="box-sizing: inherit; line-height: 0; position: relative; vertical-align: baseline; bottom: -0.25em; color: rgb(33, 33, 33); font-family: BlinkMacSystemFont, -apple-system, "Segoe UI", Roboto, Oxygen, Ubuntu, Cantarell, "Fira Sans", "Droid Sans", "Helvetica Neue", sans-serif;">6N<span style="box-sizing: inherit; line-height: 0; position: relative; vertical-align: baseline; bottom: -0.25em; color: rgb(33, 33, 33); font-family: BlinkMacSystemFont, -apple-system, "Segoe UI", Roboto, Oxygen, Ubuntu, Cantarell, "Fira Sans", "Droid Sans", "Helvetica Neue", sans-serif;">2O or [Ag(2AB)<span style="box-sizing: inherit; line-height: 0; position: relative; vertical-align: baseline; bottom: -0.25em; color: rgb(33, 33, 33); font-family: BlinkMacSystemFont, -apple-system, "Segoe UI", Roboto, Oxygen, Ubuntu, Cantarell, "Fira Sans", "Droid Sans", "Helvetica Neue", sans-serif;">2]NO<span style="box-sizing: inherit; line-height: 0; position: relative; vertical-align: baseline; bottom: -0.25em; color: rgb(33, 33, 33); font-family: BlinkMacSystemFont, -apple-system, "Segoe UI", Roboto, Oxygen, Ubuntu, Cantarell, "Fira Sans", "Droid Sans", "Helvetica Neue", sans-serif;">3·(2AB)<span style="box-sizing: inherit; line-height: 0; position: relative; vertical-align: baseline; bottom: -0.25em; color: rgb(33, 33, 33); font-family: BlinkMacSystemFont, -apple-system, "Segoe UI", Roboto, Oxygen, Ubuntu, Cantarell, "Fira Sans", "Droid Sans", "Helvetica Neue", sans-serif;">2, was synthesized from ethanol solutions of AgNO<span style="box-sizing: inherit; line-height: 0; position: relative; vertical-align: baseline; bottom: -0.25em; color: rgb(33, 33, 33); font-family: BlinkMacSystemFont, -apple-system, "Segoe UI", Roboto, Oxygen, Ubuntu, Cantarell, "Fira Sans", "Droid Sans", "Helvetica Neue", sans-serif;">3 and 2AB. The asymmetric unit contains one mol-ecule of [Ag(2AB)<span style="box-sizing: inherit; line-height: 0; position: relative; vertical-align: baseline; bottom: -0.25em; color: rgb(33, 33, 33); font-family: BlinkMacSystemFont, -apple-system, "Segoe UI", Roboto, Oxygen, Ubuntu, Cantarell, "Fira Sans", "Droid Sans", "Helvetica Neue", sans-serif;">2]NO<span style="box-sizing: inherit; line-height: 0; position: relative; vertical-align: baseline; bottom: -0.25em; color: rgb(33, 33, 33); font-family: BlinkMacSystemFont, -apple-system, "Segoe UI", Roboto, Oxygen, Ubuntu, Cantarell, "Fira Sans", "Droid Sans", "Helvetica Neue", sans-serif;">3·(2AB)<span style="box-sizing: inherit; line-height: 0; position: relative; vertical-align: baseline; bottom: -0.25em; color: rgb(33, 33, 33); font-family: BlinkMacSystemFont, -apple-system, "Segoe UI", Roboto, Oxygen, Ubuntu, Cantarell, "Fira Sans", "Droid Sans", "Helvetica Neue", sans-serif;">2, The central silver(I) atom is coordinated by two nitro-gen donor atoms from 2-amino-benzaxazole ligands in an N<span style="box-sizing: inherit; line-height: 0; position: relative; vertical-align: baseline; bottom: -0.25em; color: rgb(33, 33, 33); font-family: BlinkMacSystemFont, -apple-system, "Segoe UI", Roboto, Oxygen, Ubuntu, Cantarell, "Fira Sans", "Droid Sans", "Helvetica Neue", sans-serif;">2 coordination set while another two 2-amino-benzaxazole ligands and one nitrate anion remain uncoordinated. The crystal structure features several intra-molecular N-H⋯O and N-H⋯N hydrogen-bonding inter-actions as well as C-H⋯π, Ag⋯π and π-π inter-actions between adjacent AB ligands. Hirshfeld surface analysis and two-dimensional fingerprint plots were used to investigate the inter-molecular inter-actions.

Synthesis, crystal structure and Hirshfeld surface analysis of bis[2-amino-5-(ethylsulfanyl)-1,3,4-thiadiazol-3-ium] bis(perchlorato-κO)bis(picolinato-κ2N,O)copper(II) - Khojabaeva, Gulnaz; Torambetov, Batirbay; Gonnade, Rajesh G.; Uzakbergenova, Zamira; Rasulov, Abdusamat; Kadirova, Shakhnoza (Acta Crystallographica Section E, Crystallographic Communications, 2025)

Synthesis, crystal structure, DFT calculation and catalytic activity of a polymer complex of zinc(II) succinate with 2-amino-1,3,4-thiadiazole - Nuralieva, Guzal; Alieva, Mushtariy; Torambetov, Batirbay; Leslee, Denzil Britto Christopher; Senthilkumar, Beeran; Kaur, Simranjeet; Dabke, Niteen B.; Vanka, Kumar; Ashurov, Jamshid; Kadirova, Shakhnoza; Gonnade, Rajesh G. (Journal of Molecular Structure, 2025)
A polymer complex of zinc(II) succinate with a 2-amino-1,3,4-thiadialole ligand, denoted as [Zn2L2(suc)2]n, was synthesized and characterized by NMR, ESI-MS, FTIR, and FT-Raman spectroscopy, TGA, and X-ray crystallography. The polymer complex crystallizes in the orthorhombic noncentrosymmetric Pna21 space group and features a five-coordinate zinc ion in a distorted spherical square pyramidal geometry. The Hirshfeld surface analysis was carried out to evaluate the intermolecular interactions. Additionally, computational studies were also conducted to assess the stability of the Zn polymer complex and analyze the electron density distribution of the HOMO and LUMO. The catalytic activity of our complex was tested, interestingly, that showed good results for Biginelli reactions with distinct substrate scope in good to high yield at mild reaction conditions.
Keywords: DFT; Dihydropyrimidinones; Polymer complex; succinate; Thiadiazole; zinc

Synthesis, crystal structure, Hirshfeld surface analysis and DFT calculations of the coordination compound tetraaquabis2-[(5-methyl-1,3,4-thiadiazol-2-yl)sulfanyl]acetato-κOcobalt(II) - Kinshakova, Ekaterina; Torambetov, Batirbay; Kaur, Simranjeet; Ashurov, Jamshid; Kadirova, Shakhnoza (Acta Crystallographica Section E Crystallographic Communications, 2025)
A relatively strong hydrogen bond between one of the water molecules and the non-coordinating carboxylate O atom consolidates the conformation. In the crystal, intermolecular hydrogen bonds lead to the formation of a complex tri-periodic structure. Hirshfeld surface analysis revealed that 30.1% of the intermolecular interactions are from H⋯H contacts and 20.8% are from N⋯H/H⋯N contacts. DFT calculations were performed to assess the stability and chemical reactivity of the compound by determining the energy differences between the HOMO and LUMO.

Transition metal complexes of Thiadiazole-Picolinic acid: Crystal structures, DFT insights and anticancer activity - Torambetov, Batirbay; Khojabaeva, Gulnaz; Bharty, M. K.; Gupta, Sushil K.; Kadirova, Shakhnoza; Pradeep, S.; Dastager, Syed G.; Gonnade, Rajesh G. (Journal of Molecular Structure, 2026)
Five novel transition metal complexes [Ni(H2aeth)2(Pic)2] (1), [Co(H2aeth)2(Pic)2] (2), [Ni(H2aeth)2(Pic)(HPic)] ClO4 (3), [Co(H2aeth)2(Pic)(HPic)]ClO4 (4) and [Zn(H2aeth)2 (Pic)(HPic)]ClO4 (5) were synthesized using a 2amino-5-ethylthio-1,3,4-thiadiazole (H2aeth) and picolinic acid (HPic) as co-ligands. These complexes were characterized by FT-IR, UV-Vis., X-ray photoelectron spectroscopy, TG-DTA, and single-crystal X-ray techniques. Crystallographic analysis confirmed distorted octahedral geometries around the metal centers with extensive hydrogen bonding networks promoting supramolecular assembly in the solid state. X-ray photoelectron spectroscopy (XPS), validated the +2 oxidation state of each metal center. Thermal studies indicated multistep decomposition processes resulting in the formation of metal oxides. Density functional theory (DFT) and timedependent DFT calculations were employed to explore electronic structures and predict UV-Vis. transitions, which showed good agreement with experimental data. Frontier molecular orbital (FMO) analysis revealed that Ni(II) complexes 1 and 3 are softer and more reactive, consistent with their observed biological activity. The anticancer potential of complexes 1-5 was evaluated in vitro using the MCF-7 human breast cancer cell line and the MTT assay. Complex 1 exhibited the strongest cytotoxicity (IC50 = 26.5 mu g/mL) followed by complexes 3 (34.9 mu g/mL), 4 (46.4 mu g/mL), 2 (81.1 mu g/mL), and 5 (103.3 mu g/mL). The observed activity trends correlate with metal identity and coordination environment, underlining the role of electronic and structural factors in modulating bioactivity. These findings suggest that thiadiazole-picolinate metal complexes, particularly those based on Ni (II), are promising scaffolds for anticancer drug development.
Keywords: Anti-cancer activity; crystal structure; DFT calculation; MCF-7 cell line; Picolinic acid; Thiadiazole complexes